Correlation between inclination of the acetabular component and metal ion levels in metal-on-metal hip resurfacing replacement. - De Haan, R; Pattyn, C; Gill, H; Murray, D; Campbell, P; De Smet, K (2008)
We examined the relationships between the serum levels of chromium and cobalt ions and the inclination angle of the acetabular component and the level of activity in 214 patients implanted with a metal-on-metal resurfacing hip replacement. Each patient had a single resurfacing and no other metal in their body. All serum measurements were performed at a minimum of one year after operation. The inclination of the acetabular component was considered to be steep if the abduction angle was greater than 55 degrees. There were significantly higher levels of metal ions in patients with steeply-inclined components (p = 0.002 for chromium, p = 0.003 for cobalt), but no correlation was found between the level of activity and the concentration of metal ions. A highly significant (p < 0.001) correlation with the arc of cover was found. Arcs of cover of less than 10 mm were correlated with a greater risk of high concentrations of serum metal ions. The arc of coverage was also related to the design of the component and to size as well as to the abduction angle of the acetabular component. Steeply-inclined acetabular components, with abduction angles greater than 55 degrees, combined with a small size of component are likely to give rise to higher serum levels of cobalt and chromium ions. This is probably due to a greater risk of edge-loading.